Significance of silica analysis in groundwater in parts of Central Ganga Plain, Uttar Pradesh, India - Mohammad Muqtada Ali Khan; Rashid Umar (2010)
A study on variation in silica values in groundwater from a small part of the Central Ganga Plain has yielded valuable information on relative roles of geogenic and anthropogenic solute acquisition processes and depth to the deep aquifer system in the area. It is recommended that silica analysis should be a mandatory component of all systematic hydrogeochemical studies.